1987
DOI: 10.1093/mnras/225.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Narrow polarized components in the OH 1612-MHz maser emission from supergiant OH–IR sources

Abstract: High-resolution OH 1612-MHz spectra are presented of the supergiant OH-IR sources VY CMa, VX Sgr, IRC 10420 and NML Cyg. The spectra have a resolution of 300 Hz. Narrow components in the spectra have linewidths as small as 550 Hz (0.1 km s-1) but there is no evidence for components narrower than this. These results are in accord with present understanding of maser line-narrowing and of the physical conditions in the OH maser regions. Many of the narrow components have an appreciable degree of circular pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Indeed, since it is very unlikely that the magnetic field energy density in the wind is larger than its kinetic energy density, i.e., B 2 /8π ≤ ρv 2 w /2, we should expect a magnetic field not in excess of B ≤ 3.4 mG at r ∼ 3 × 10 16 cm (if it arises from a compression of the magnetic field in the wind). This value of the magnetic field is in agreement with the values obtained from polarization observations of OH masers in supergiants (e.g., Cohen et al 1987;Nedoluha & Bowers 1992), which give magnetic field estimates at distances of ∼3 × 10 16 cm of ∼1−10 mG. However, we find that the magnetic field is actually about 0.58 G, i.e., 170 times larger.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, since it is very unlikely that the magnetic field energy density in the wind is larger than its kinetic energy density, i.e., B 2 /8π ≤ ρv 2 w /2, we should expect a magnetic field not in excess of B ≤ 3.4 mG at r ∼ 3 × 10 16 cm (if it arises from a compression of the magnetic field in the wind). This value of the magnetic field is in agreement with the values obtained from polarization observations of OH masers in supergiants (e.g., Cohen et al 1987;Nedoluha & Bowers 1992), which give magnetic field estimates at distances of ∼3 × 10 16 cm of ∼1−10 mG. However, we find that the magnetic field is actually about 0.58 G, i.e., 170 times larger.…”
Section: Resultssupporting
confidence: 91%
“…The polarization information is not available or neglected in the interferometric surveys of the Galactic plane (Sevenster et al 1997a(Sevenster et al ,b, 2001) in numerous single-dish studies of IRAS colour-selected objects (e.g., Eder et al 1988;Le Squeren et al 1991;te Lintel Hekkert et al 1991) and in earlier blind surveys (e.g., Bowers 1978;Baud et al 1979a,b). Earlier studies (e.g., Wilson et al 1970;Wilson & Barrett 1972) suggested that the 1612 MHz circumstellar emission is essentially unpolarized but the observations with a spectral resolution better than 0.1 km s −1 revealed several circularly polarized features (Cohen et al 1987;Zell & Fix 1991). The OH emission in the 1665 and 1667 MHz lines shows a substantial degree of circular polarization up to 50−80% Claussen & Fix 1982) but linear polarization occurs in only ∼10% of sources (Olnon et al 1980).…”
Section: Introductionmentioning
confidence: 92%
“…This finding is at odds with early reports, which demonstrated a paucity of polarized features in the 1612 MHz spectra and only occasional detections of linear polarization at 1667 MHz (Cohen 1989, for review). Thus, spectral resolution appears to be a crucial factor (Cohen et al 1987;Zell & Fix 1991).…”
Section: Occurence Of Polarizationmentioning
confidence: 99%
“…Such effects are not seen in normal AGB stars (e.g., Cohen et al 1987). The variability of upto a factor of 2 suggests the effect may be related to line overlap between different Zeeman components along the line of sight (Deguchi & Watson 1986).…”
Section: Summary: the Two Componentsmentioning
confidence: 94%